Kesenian Jaran Kepang sebagai Identitas Masyarakat Kediri: Partisipasi Pemuda dalam Melestarikan Kesenian Jaran Kepang - Afifah, Talitha; Samidi; Mochtar Lutfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze youth participation in the preservation of Jaran Kepang art through the Rogo Samboyo Putro (RSP) Paguyuban in Kediri Regency, East Java, as well as its role in maintaining local cultural identity in the midst of globalization. Using a descriptive qualitative approach, research data were obtained through observation, in-depth interviews, and documentation. The analysis was conducted by referring to Stuart Hall's cultural identity theory, which views cultural identity as a fixed form (identity as being) and an ever-evolving process (identity as becoming). The results showed that youth have a very important contribution to the preservation of Jaran Kepang through four types of participation, namely decision-making, activity implementation, evaluation, and benefit distribution. The RSP Association is a forum for passing on traditional arts while modernizing costumes and promotion through social media. A structured organizational structure, a culture of deliberation, and a sustainable work program strengthen the role of youth in developing Jaran Kepang art. Thus, the art of Jaran Kepang not only functions as a cultural heritage, but also transforms according to the times, so that it remains relevant as a reinforcement of the identity of the Kediri community.